A Detailed Analysis of the Dynamic Behavior of a MEMS Vibrating Internal Ring Gyroscope - Waqas Amin Gill; Ian Howard; Ilyas Mazhar; Kristoffer McKee (Micromachines, 2024)
This paper presents the development of an analytical model of an internal vibrating ring gyroscope in a Microelectromechanical System (MEMS). The internal ring structure consists of eight semicircular beams that are attached to the externally placed anchors. This research work analyzes the vibrating ring gyroscope’s in-plane displacement behavior and the resulting elliptical vibrational modes. The elliptical vibrational modes appear as pairs with the same resonance frequency due to the symmetric structure of the design. The analysis commences by conceptualizing the ring as a geometric structure with a circular shape possessing specific dimensions such as thickness, height, and radius. We construct a linear model that characterizes the vibrational dynamics of the internal vibrating ring. The analysis develops a comprehensive mathematical formulation for the radial and tangential displacements in local polar coordinates by considering the inextensional displacement of the ring structure. By utilizing the derived motion equations, we highlight the underlying relationships driving the vibrational characteristics of the MEMS’ vibrating ring gyroscope. These dynamic vibrational relationships are essential in enabling the vibrating ring gyroscope’s future utilization in accurate navigation and motion sensing technologies.